Effects of a Ferulate-Derived Dihydrobenzofuran Neolignan on Angiogenesis, Steroidogenesis, and Redox Status in a Swine Cell Model. (October 2014) - Basini, Giuseppina; Spatafora, Carmela; Tringali, Corrado; Bussolati, Simona; Grasselli, Francesca
In the ongoing search for new therapeutic compounds, lignans and neolignans, which are widely distributed in plants, deserve special attention because of their interactions with several biological targets. Searching for potential antiangiogenic agents related to natural lignans/neolignans, we were attracted by a previously studied synthetic dihydrobenzofuran neolignan. We synthesized the compound by means of an eco-friendly, enzyme-mediated biomimetic coupling of the methyl ester of ferulic acid, and the present study was aimed to deeply investigate its effect in angiogenesis bioassays validated in our laboratory. In addition, a previously well-defined granulosa cell model was employed to evaluate the effect of dihydrobenzofuran neolignan on cell viability, steroidogenesis, and redox status. Present data support the antiangiogenic effect of this neolignan. Moreover, we demonstrate that, at least at the highest concentrations tested, dihydrobenzofuran neolignan affects granulosa cell viability and steroidogenesis. In addition, the compound inhibits generation of free radicals and stimulates scavenger enzyme activities. The present data, which are a further deepening of the evaluation of the biological activities of the dihydrobenzofuran lignan in well-defined cell models, are of interest and worthy of special attention.